1997
DOI: 10.1086/304434
|View full text |Cite
|
Sign up to set email alerts
|

Dust in the Small Magellanic Cloud: Interstellar Polarization and Extinction

Abstract: The typical extinction curve for the Small Magellanic Cloud (SMC), in contrast to that for the Galaxy, has no bump at 2175Å and has a steeper rise into the far ultraviolet. For the Galaxy the interpretation of the extinction and, therefore, the dust content of the interstellar medium has been greatly assisted by measurements of the wavelength dependence of the polarization. To the present no such measurements existed for the SMC.Therefore, to further elucidate the dust properties in the SMC we have for the fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 85 publications
5
53
0
7
Order By: Relevance
“…Thanks to this relation the dust-to-gas ratio increases with metallicity, as nicely summarized by Brinchmann et al (2013). Indeed, for the Milky Way it is about three times greater than for the Large Magellanic Cloud and ∼1.5 times greater than for the Small Magellanic Cloud, as a direct consequence of the differences in metallicity between these three galaxies (e.g., Bohlin et al 1978;Fitzpatrick 1986;Rodrigues et al 1997). In this case the galactocentric decrease of the abundance may induce a similar gradient for the dust attenuation.…”
Section: Discussionmentioning
confidence: 81%
“…Thanks to this relation the dust-to-gas ratio increases with metallicity, as nicely summarized by Brinchmann et al (2013). Indeed, for the Milky Way it is about three times greater than for the Large Magellanic Cloud and ∼1.5 times greater than for the Small Magellanic Cloud, as a direct consequence of the differences in metallicity between these three galaxies (e.g., Bohlin et al 1978;Fitzpatrick 1986;Rodrigues et al 1997). In this case the galactocentric decrease of the abundance may induce a similar gradient for the dust attenuation.…”
Section: Discussionmentioning
confidence: 81%
“…Rodrigues et al (1997) carried out polarization studies of the interstellar dust in the Small Magellanic Cloud (SMC) and concluded that it could harbour smaller dust grains than the Milky Way. They suggest that the SMC may be rich in grains with size smaller than 0.05 µm.…”
Section: Implications For Grainsmentioning
confidence: 99%
“…There is evidence that the dust grain size distributions in the SMC and the Milky Way are different (Rodrigues et al 1997;Weingartner & Draine 2001;Gordon et al 2003), and that low metallicity galaxies in general may have an excess of small dust grains relative to the Milky Way. These differences, however, should not affect our measurements of the PAH fraction.…”
Section: Parametermentioning
confidence: 99%